Permeability Structure of the Lava‐Dike Transition of 15‐Myr‐Old Oceanic Crust Formed at the East Pacific Rise - L. A. Gilbert; L. Crispini; P. Tartarotti; M. L. Bona (Geochemistry, Geophysics, Geosystems, 2018)
Abstract The permeability structure of oceanic crust controls both the spatial and temporal extent of hydrothermal circulation, but the detailed geometry of fractures in seafloor rocks is not well known. We apply an equivalent channel model to veins, joints, faults, and breccias preserved in recovered cores from ODP‐IODP Hole 1256D to calculate paleo‐permeability. In the ~250‐m transition between dikes and lavas, paleo‐permeability is 10−13~10−14 m2 with narrow zones of >10−9 m2 that presumably act as conduits for the largest volume of fluids. Most of these high‐permeability zones are oriented vertically as a result of diking events into a significant thickness of lavas outside of the neovolcanic zone. After an increase in permeability due to off‐axis diking events, fluid temperatures drop, pathways are sealed, and the permeability of the upper oceanic crust drops significantly.